TRANSISI FASA TITATNIUM OKSIDA MELALUI KONDENSASI EX-SITU HIDROGEN TITANAT TIPE STRUKTUR LEPIDOKSROSIT - Hari Sutrisno; Sunarto Sunarto (Jurnal Penelitian Saintek, 2010)
The objectives of the research are to study of the structure type of titanium dioxide (TiO2) obtained form the ex-situ condensation of hydrated hydrogen titanates with the structure type of lepidocrocite. Hydrated hydrogen titanates were obtained by ion exchabge of H+ for Cs+ in cesium titanates by 1 M HCl solution by Chimie Douce method. The results show that TiO2 (B), anatase, and anatase-rutile mixture were obtained heat treatment of hydrated hydrogen titanate at 100, 200, 300, 500, and 600oc respectively. The powders were characterized by X-rays diffractometer (XRD), High Resolution Scanning Electron Microscopy (HRSEM) and High Resolution Transmission Electron Microscopy (HRTEM). The research indicated that the protonic titanate, H0.54 Ti1.865 0.135O4 0.5H2O ( =vacancy), lost the interlayer water by being heated up to 200oC to produce a dehydrated phase, H0.54 Ti1.865 0.135O4. Above 300oC, the dehydrated phase completely transformed to TiO2(B) and anatase was obtained as pure phase at 600oC. The phase transformed as the following process: H0.54Ti1.865 0.135O4 0.5H2O à H0.54Ti1.865 0.135O4 0.25H2Oà H0.54Ti1.865 0.135O4 à TiO2(B) à TiO2-anatase.